Inquiry-Based Learning in a Digital Environment for 21st-Century Skills in Physics Course: a Review of Recent Research - Novitra, Fuja; Al Farisi, Salman; Angreni, Siska (PILLAR OF PHYSICS EDUCATION, 2024)
Inquiry-based learning (IBL) and 21st-century skills have received significant attention from educational researchers and practitioners in the field of physics education. With numerous studies affirming the positive effects of IBL, an increasing number of researchers are exploring IBL to foster various competencies within schools. However, little is known about how IBL in digital environments can influence students' 21st-century skills. This paper reviews recent literature on IBL and identifies a substantial body of research targeting enhancements in 21st-century skills resulting from IBL in digital settings. Findings indicate that integrating IBL with digital elements holds considerable potential to enrich learning experiences and develop 21st-century skills. The conceptual framework of such learning is grounded in theories of learning such as constructivism, cognitive theory, experiential learning, and connectivism. The instructional structure should be configured to has a balance between scientific processes and technological integration. This study also offers valuable insights for researchers, instructional designers, and educators in the field of physics education involved in the design and implementation of IBL in digital environments.